Pengaruh Country Of Origin, Perceived Quality, Dan Brand Image Terhadap Purchase Intention (Studi Kasus Pada Konsumen Pengguna Smartphone Samsung Di Kota Bandung) - jodi muhaqi; Anny Nurbasari (Jurnal Sekretaris dan Administrasi Bisnis, 2024)
Indonesia is one of the countries withhuge numbers of Internet users. Indonesia's population of 250 million is a big market. Indonesian smartphone users are alsoproliferating. One of the smartphone market leaders is Samsung. This study aimed to determine the effect of country of origin, perceived quality, and brand image on purchase intention. The research design used in this research is causal explanatory. The samplehas beenusing a Samsung Smartphone for more than 1 year and is a student. the number of respondents used is 130 respondents. Based on the results of the study, there is an influence of Country of origin on Purchase Intention of Samsung Smartphone users. There is an influence of Perceived quality on the Purchase Intention of Samsung Smartphone users. There is an influence of Brand image onthePurchase Intention of Samsung Smartphone users. For this reason, researchers suggest Samsung smartphones, to be able to improve Country of origin, Perceived quality, and Brand image as variables that can encourage consumer Purchase Intentions.